2020
DOI: 10.3389/fphy.2020.00163
|View full text |Cite
|
Sign up to set email alerts
|

Stock Network Stability After Crashes Based on Entropy Method

Abstract: This paper studies the stability of stock networks after crashes based on the entropy method. By measuring network stability using the entropy calculated with the degree distribution, we find that the entropy of a stock network is close to that of the Erdös-Rényi and Watts-Strogatz networks. We further introduce government rescue policies as a natural experiment and use the entropy measurement to study the influence of rescue policies after crashes on the network stability, finding that rescue policies only ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Based on network theory, all system components can be linked by their interactions to form a network; exploring global network topologies helps quantify their interconnectedness to build early warning indicators [10]. Various studies of bank, guarantee, and stock networks have found empirical evidence that global network topologies can reveal financial crises [11][12][13][14]. However, a small portion of research has emphasized that more informative signals may hide in tiny changes of local network topologies [15] because networks in similar global topologies may differ noticeably at a local level [16].…”
Section: Introductionmentioning
confidence: 99%
“…Based on network theory, all system components can be linked by their interactions to form a network; exploring global network topologies helps quantify their interconnectedness to build early warning indicators [10]. Various studies of bank, guarantee, and stock networks have found empirical evidence that global network topologies can reveal financial crises [11][12][13][14]. However, a small portion of research has emphasized that more informative signals may hide in tiny changes of local network topologies [15] because networks in similar global topologies may differ noticeably at a local level [16].…”
Section: Introductionmentioning
confidence: 99%